2012
DOI: 10.1139/o2012-014
|View full text |Cite
|
Sign up to set email alerts
|

Domain specific overexpression of TIMP-2 and TIMP-3 reveals MMP-independent functions of TIMPs duringXenopus laevisdevelopment

Abstract: Extracellular matrix remodelling mediates many processes including cell migration and differentiation and is regulated through the enzymatic action of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs). TIMPs are secreted proteins, consisting of structurally and functionally distinct N- and C-terminal domains. TIMP N-terminal domains inhibit MMP activity, whereas their C-terminal domains may have cell signalling activity. The in vivo role of TIMP N- and C-terminal domains in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Using semiquantitative RT-PCR, we assayed for changes in mRNA levels of the MMP inhibitors (TIMP-2, TIMP-3, and RECK), as well as the MMPs (MMP-2, MMP-9, and MT1-MMP). All of these genes have previously been shown to be important regulators of ECM remodeling during development [8, 9, 12, 34]. mRNA levels were normalized to Ef1 α and compared to control (uninjected) embryos.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using semiquantitative RT-PCR, we assayed for changes in mRNA levels of the MMP inhibitors (TIMP-2, TIMP-3, and RECK), as well as the MMPs (MMP-2, MMP-9, and MT1-MMP). All of these genes have previously been shown to be important regulators of ECM remodeling during development [8, 9, 12, 34]. mRNA levels were normalized to Ef1 α and compared to control (uninjected) embryos.…”
Section: Resultsmentioning
confidence: 99%
“…At the present time there is comparatively little research characterizing the roles of the N- and C-terminal TIMP domains in vivo , particularly as they pertain to development. Our lab has previously examined the specific functions of the N- and C-terminal domains of TIMP-2 and -3 during X. laevis development and found that the two domains have unique functions when overexpressed individually in X. laevis embryos [12]. To date, there has been no comparison of the unique functions of TIMP-1 N- and C-terminal domains in a developmental context.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations